Industrial Location in Developing Countries. - Deichmann, U; Lall, S; Redding, S; Venables, A (2008)
Despite a diminishing role in industrial countries, the manufacturing sector continues to be an engine of economic growth in most developing countries. This article surveys the evidence on the determinants of industry location in developing countries. It also employs micro data for India and Indonesia to illustrate recent spatial dynamics of manufacturing relocation within urban agglomerations. Both theory and empirical evidence suggest that agglomeration benefits, market access, and infrastructure endowments in large cities outweigh the costs of congestion, higher wages, and land prices. Despite this evidence, many countries have tried to encourage industrial firms to locate in secondary cities or other lagging areas. Cross-country evidence suggests that fiscal incentives to do so rarely succeed. They appear to influence business location decisions among comparable locations, but the result may be a negative-sum game between regions and inefficiently low tax rates, which prevent public goods from being funded at sufficiently high levels. Relocation tends to be within and between agglomerations rather than from large cities to smaller cities or lagging regions. Rather than provide subsidies and tax breaks, policymakers should focus on streamlining laws and regulations to make the business environment more attractive.